Slang Words Used in Movie Script “Harold and Kumar Go to White Castle” - Putrawan, I Made Yudhi; Sudipa, I Nengah; Sukarini, Ni Wayan (Humanis; Vol 24 No 2 (2020)DO - 10.24843/JH.2020.v24.i02.p06, 2020)
The title of this study is Slang Word Used in Movie Script “Harold And Kumar Go to White Castle”.  The aims of the study are to identify the types of slang and meaningconveyed in movie script Harold and Kumar Go to White Castle. The data of this study were collected from” Harold and Kumar Go to White Castle” movie script as the data source. The theories usedin the study are theory proposed by Allan and Burridge (2006) entitled Forbidden words: Taboo and The Censoring of Language used to identify the types of slang word, and theory proposed by by Leech (1974) entitled Study of Meaning used to analyze the meaningsconveyed in the movie. The documentation method is used to collect the data, and descriptive qualitative method is used to analyze the data.There were forty slangs either in the form of words or phrases that areanalyzed based on theorymentioned above. There are five types of slang in theory of Allan and Burridge (2006) but only four types were found in the movie script.  Those are fresh and creative, imitative, flippant, acronym, and clipping. Flippant type was the most found in the data source. For the meaning, there were seven types of meaning based on thetheory proposed byLeech (1974) but only six types were found in the movie script. Those are conceptual meaning, connotative meaning, social meaning, collocative meaning, reflected meaning, and affective meaning. Affective meaning type is the most found in the data source.